College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter R - Section R.7 - Rational Expressions - R.7 Assess Your Understanding - Page 71: 59


LCM = $x^{3}(2x-1)^{2}$

Work Step by Step

Step 1: Factor each polynomial completely. $ 4x^{3}-4x^{2}+x=x(4x^{2}+4x+1)=\qquad$ ... recognize perfect square $=\boxed{x(2x-1)^{2}}$ $2x^{3}-x^{2}=\boxed{x^{2}(2x-1)}$ $x^{3}=\boxed{x^{3}}$ Step 2: The LCM is the product of each of these factors raised to a power equal to the greatest number of times that the factor occurs in the polynomials. LCM = $x^{3}(2x-1)^{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.